Sustainable quantum dot chemistry: effects of precursor, solvent, and surface chemistry on the synthesis of Zn3P2 nanocrystals. Issue 22 (21st February 2020) - Swain, Robert A.; McVey, Benjamin F. P.; Virieux, Héloïse; Ferrari, Fabio; Tison, Yann; Martinez, Hervé; Chaudret, Bruno; Nayral, Céline; Delpech, Fabien
Abstract : The synthesis of Zn3 P2 nanocrystals of unprecedented quality was performed using novel zinc precursors. Abstract : The quest of exploring alternative materials for the replacement of toxic cadmium- and lead-based quantum dots (QDs) is necessary for envisaging a sustainable future but remains highly challenging. Tackling this issue, we present the synthesis of Zn3 P2 nanocrystals (NCs) of unprecedented quality. New, reactive zinc precursors yield highly crystalline, colloidally stable particles, exhibiting oxide-free surfaces, size tunability and outstanding optical properties relative to previous reports of zinc phosphide QDs.